Chapter Lagoon scenarios for the Bassa Friulana plain: a flooding archipelago - VENUDO, ADRIANO (Proceedings e report, 2020)
The paper first focuses on morphological history of a landscape unit, consisting of biological deserts and wrecks of the endangered landscape. Secondly, it analyzes and elaborates hydrological scenarios to explore and discuss potential design strategies. Water margin continuity could be recovered through development of flooding strategies. In conclusion, form of the archipelago emerges as a specificity of the landscape unit. More than a metaphor but as a conceptual and programmatic dispositive, archipelago can inform on dynamic structure of the Bassa Friulana complex system within an ecological framework.